Water safety training as a potential means of reducing risk of young children's drowning. Issue 4 (December 1995) - Asher, K. N.; Rivara, F. P.; Felix, D.; Vance, L.; Dunne, R.
Abstract : OBJECTIVES: To determine the effects of training in swimming and water safety on young preschool-children's ability to recover safely from a simulated episode of falling into a swimming pool. DESIGN: Randomized trial of 12 or eight weeks' duration water safety and swimming lessons for children 24 to 42 months old. OUTCOME MEASURES: Swimming ability, deck behavior, water recovery, and swimming to side after jumping into pool were measured before, during, and after the training program. RESULTS: 109 children completed the study (61 in the 12 week group, 48 in the eight week group). The average age was 34.2 months, 54% were male. Swimming ability, deck behavior, water recovery, and jump and swim skills improved over baseline levels in both groups. By the end of training, the 12 week group improved more than the eight week group only in swimming ability. Improvements in water recovery and jump and swim skills were associated positively with changes in swimming ability. CONCLUSIONS: Swimming ability and safety skills of young preschool children can be improved through training. Such programs may offer some protection for children at risk of drowning and there was no indication that this program increased the risk of drowning. However, pool fencing, other barriers around water, and parental supervision still remain the most important prevention strategies to reduce drowning in young children.